An Adaptive Web-Based Learning Environment - Angelakis, George (Trinity College Dublin. Department of Computer Science, 2000)
In recent years enormous progress has been made in World Wide Web technologies. This is making the web an even more promising way to deliver educational material. New Technology, integrated with experiential education, can increase the effectiveness and efficiency of the learning process. Java Servlets, XML, XSL, CSS and Java applets make dynamic creation of web pages, easier and richer. User profiles are widely used in learning environments contributing new approaches in the way computers are used to deliver education. Profiles can be built with information requested directly from the learners or from analysis of the way learners interact with the learning environment.

This thesis focuses on the creation of a flexible and rich environment, which can be used to improve the quality and power of web based learning. It presents a distributed approach to the design and implementation of an improved learning environment. Both instructional and assessment material will be generated dynamically for each user upon request. The system will be adaptive to users' profiles, so that users with different profiles may be presented with different content. Users will have control over their profiles. Additionally, it will be possible for the system to automatically update a profile. The pages containing the material will be made up of modules. Modules can be html, text, applets or multimedia files.

A prototype system will be created for the instruction of Mathematics for secondary education. The system will be available over the World Wide Web. A Microsoft Access DBMS will be used for the storage of students' profiles, instructional and assessment materials. Java Servlets and JDBC will be used for the connection to the database and the creation of all the Web pages
Keywords: Computer Science